Assessment of tomato and wine processing solid wastes as soil amendments for biosolarization. (February 2016) - Achmon, Yigal; Harrold, Duff R.; Claypool, Joshua T.; Stapleton, James J.; VanderGheynst, Jean S.; Simmons, Christopher W.
Graphical abstract: Highlights: The biosolarization potential of tomato and grape processing wastes were assessed. Simulated biosolarization gauged pest inactivation mechanisms in amended soil. Tomato and white wine wastes led to significant soil heating and acidification. Oxygen availability influenced the magnitude of soil heating and acidification. Red wine waste did not induce pest inactivation conditions during biosolarization. Abstract: Pomaces from tomato paste and wine production are the most abundant fruit processing residues in California. These residues were examined as soil amendments for solarization to promote conditions conducive to soil disinfestation (biosolarization). Simulated biosolarization studies were performed in both aerobic and anaerobic soil environments and soil temperature elevation, pH, and evolution of CO2, H2 and CH4 gases were measured as metrics of soil microbial activity. Tomato pomace amendment induced conditions associated with soil pest inactivation, including elevation of soil temperature by up to 2 °C for a duration of 4 days under aerobic conditions and a reduction of soil pH from 6.5 to 4.68 under anaerobic conditions. White wine grape pomace amendment showed similar trends but to a lesser extent. Red wine grape pomace was generally less suitable for biosolarization due to significantly lower soil temperature elevations, reduced acidification relative to the other pomaces and induction of methanogenesis in the soil.